National Heroes in Indonesian History Text Book (History Department, Semarang State University and Historian Society of Indonesia, 2019)
History education has an essential role in building the character of society. One of the advantages of learning history in terms of value inculcation is the existence of a hero who is made a role model. Historical figures become best practices in the internalization of values. However, the study of heroism and efforts to instill it in history learning has not been done much. Therefore, researchers are interested in reviewing the values of bravery and internalization in education. Through textbook studies and curriculum analysis, researchers can collect data about national heroes in the context of learning. The results showed that not all national heroes were included in textbooks. Besides, not all the heroes mentioned in the book are specifically reviewed. There are only a few heroes that are specifically reviewed because they have links to basic competencies in the 2013 curriculum. The most popular heroes in the history textbook are (1) Pattimura, (2) Diponegoro, (3) Sukarno, (4) Mohammad Hatta, (5) Hamengkubuwono IX. This hero is mostly reviewed for KD class XI numbers 3.2, 3.6, and 3.9. National heroes have curricular relevance, which has now been integrated into history learning. This study analyzed the position of national heroes in the compulsory Indonesian History learning curriculum at the high school level.Â Pendidikan sejarah memiliki peran penting dalam membangun karakter masyarakat. Salah satu keuntungan dari belajar sejarah dalam hal penanaman nilai adalah keberadaan pahlawan yang dijadikan panutan. Tokoh sejarah menjadi praktik terbaik dalam internalisasi nilai. Namun, studi tentang kepahlawanan dan upaya menanamkannya dalam pembelajaran sejarah belum banyak dilakukan. Oleh karena itu, peneliti tertarik untuk meninjau nilai-nilai keberanian dan internalisasi dalam pendidikan. Melalui studi buku teks dan analisis kurikulum, peneliti dapat mengumpulkan data tentang pahlawan nasional dalam konteks pembelajaran. Hasil penelitian menunjukkan bahwa tidak semua pahlawan nasional dimasukkan dalam buku teks. Selain itu, tidak semua pahlawan yang disebutkan dalam buku ini ditinjau secara khusus. Hanya ada beberapa pahlawan yang secara khusus ditinjau karena mereka memiliki kaitan ke kompetensi dasar dalam kurikulum 2013. Pahlawan paling populer dari dua buku yang dianalisis, yaitu (1) Pattimura, (2) Diponegoro, (3) Sukarno, (4) Mohammad Hatta, (5) Hamengkubuwono IX. Pahlawan ini sebagian besar relevan untuk KD kelas XI nomor 3.2, 3.6, dan 3.9. Pahlawan nasional memiliki relevansi kurikuler, yang sekarang telah diintegrasikan ke dalam pembelajaran sejarah. Penelitian ini menganalisis posisi pahlawan nasional dalam kurikulum pembelajaran Sejarah Indonesia wajib di tingkat sekolah menengah.Â